Effect of different cooking methods on nutrient composition of selected brassica family vegetables / Mazuin Che Mahmood - Che Mahmood, Mazuin Che (2008)
Numerous studies indicate that Brassica vegetables protect humans against cancer; they are rich sources of total phenolic compound and posse’s high content of vitamins and mineral nutrients. In this study, 2 types of Brassica vegetables which are broccoli and cauliflower were analyzed for its total phenolic compound, vitamin C and minerals (sodium, calcium, iron, copper and zinc). Four conventional household cooking methods, namely steaming, boiling, stir-frying and using microwave were used to evaluate the effects of cooking. Results showed that from all cooking treatment, phenolics and vitamin C were more affected than minerals. Minerals reduced slightly after the cooking treatments compare to the raw. There is significant difference (P<0.05) of sodium content between the raw and all the treatments in both samples. The calcium content did not differ significantly in raw or cooked cauliflower while calcium content in broccoli was significantly reduced (P<0.05) from raw, stir frying, using microwave, steaming and boiling, respectively. Microwaving not shows a significant effect on iron content compare to the raw in both samples. Raw broccoli (0.33 mg/100 g weight basis) has highest value of copper content compare to the raw cauliflower (0.14 mg/100 g weight basis). Zinc content in all cooking treatments slightly reduced from raw broccoli. All cooking methods produce significant loss of total phenolic, the cauliflower (81.25%) and broccoli (73.33%) which was subjected to steaming treatments. Vitamin C was destroyed to the greatest extent by boiling followed by stir frying and steaming. Microwaving did not show significant loss in vitamin C in both samples. Based on this research, Microwave cooking resulted in greater nutrient retention when compared with samples cooked by others cooking methods. Boiling resulted in highest loss of nutrient to surrounding water than other treatments.